Social skills in gifted students - Mendonça, Lurian Dionizio [UNESP]; Capellini, Vera Lucia Messias Fialho [UNESP]; Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Gastaldi, Daniel German Ramos [UNESP] (Wiley, 2025)
People with high skills have a different behavioural repertoire and generally, such characteristics define their type of gifted. However, we do not have conclusive data regarding the characteristics of this population, since it is an area of study that generates many controversies, and when it comes to socio-emotional characteristics, investigations are even more scarce and conflicting. Thus, the present study tried to describe and compare the behavioural characteristics and social abilities of students with high skills, before and after participating in enrichment activities. The Strengths and Difficulties Questionnaire (SDQ) was used, with the students themselves, their parents and teachers as informants. The results showed a good repertoire of social skills and few behaviour problems in these students, but there was no significant improvement in the second evaluation. As limitations, it was pointed out: the fact that the activities of curricular enrichment do not deal with the formal teaching of social skills; the reduced size of the sample and the lack of a control group to compare the results. As strong points, it was found that there are few studies that seek to describe the socio-emotional characteristics of this population, neglecting other needs that need to be observed and met.
Keywords: gifted; high skills; socio-emotional behavior